2014
DOI: 10.12659/msm.890478
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Early Endometrial Cancer: An Update and Proposal of a Therapeutic Algorithm

Abstract: In the last few years technical improvements have produced a dramatic shift from traditional open surgery towards a minimally invasive approach for the management of early endometrial cancer. Advancement in minimally invasive surgical approaches has allowed extensive staging procedures to be performed with significantly reduced patient morbidity. Debate is ongoing regarding the choice of a minimally invasive approach that has the most effective benefit for the patients, the surgeon, and the healthcare system a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 102 publications
(145 reference statements)
0
14
0
Order By: Relevance
“…Although some studies (ASTEC, Benedetti-Panici) [ 54 ],[ 55 ] showed no therapeutic benefit of combined pelvic and para-aortic lymphadenectomy for patients with endometrial cancer, these studies had some limitations. While in the ASTEC study, the follow-up period was short, lymphadenectomy was selective rather than systematic (nine or fewer lymph nodes were removed in 35% of patients in the lymphadenectomy group), neither of the studies included para-aortic lymphadenectomy [ 56 ],[ 57 ], which is an important site of endometrial carcinoma metastases as confirmed by sentinel lymph node investigation [ 58 ], and subsequent radiation was not tailored to the nodal status. Hence, it is difficult to draw any definite conclusion from these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies (ASTEC, Benedetti-Panici) [ 54 ],[ 55 ] showed no therapeutic benefit of combined pelvic and para-aortic lymphadenectomy for patients with endometrial cancer, these studies had some limitations. While in the ASTEC study, the follow-up period was short, lymphadenectomy was selective rather than systematic (nine or fewer lymph nodes were removed in 35% of patients in the lymphadenectomy group), neither of the studies included para-aortic lymphadenectomy [ 56 ],[ 57 ], which is an important site of endometrial carcinoma metastases as confirmed by sentinel lymph node investigation [ 58 ], and subsequent radiation was not tailored to the nodal status. Hence, it is difficult to draw any definite conclusion from these studies.…”
Section: Discussionmentioning
confidence: 99%
“…The current therapeutic standard in an early stage EC is preclusive of fertility and consists of staging total hysterectomy, bilateral salpingo-oophorectomy, and eventual pelvic and aortic lymphadenectomy [12]. …”
Section: Introductionmentioning
confidence: 99%
“…The surgical specimen will provide data such as depth of invasion, lymphovascular invasion, tumor size, and extrauterine disease (lymphadenectomy and peritoneum biopsy). Therefore, the risk of recurrence of each patient can be estimated, and then a risk-benefit analysis of adjuvant treatment can be performed [8][9].…”
Section: Introductionmentioning
confidence: 99%